Deaths Related to Vessel Injuries in Extremities - Türkmen, Nursel; Fedakar, Recep; Eren, Bülent; Saka, Naile Esra (The Bulletin of Legal Medicine, 2003)
Lethal or non-lethal extremity injuries are often seen in medico-legal practice. In this study, we planned to investigate medico-legal properties of deaths related to vessel injuries in extremities. In forensic autopsies performed in Bursa, we examined total 4242 autopsy reports between 1996-2003 in included 40 (0,94%) cases of deaths caused by vessel injuries in extremities. 90% of cases were male with median age 35.87 (17-66). Stabbing device account for 60% of injuries. Most frequent injuries were in femoral artery and branches. In 82.5% of cases, homicide was the origin of death. In 30% of cases, mean 159.33 mg/dl alcohol blood concentration was detected. In the scene investigation reports, 47.5% of documented incidents were outdoor and 47.5% of the cases died in the scene. As a conclusion, it is observed that alcoholic males of middle age are the risk group for vascular injuries in extremities. In the deaths related to isolated vessel injuries in extremities, the detection of injured vessel, localisation and number of total and lethal wounds would offer a solution for the evil intent; and as in the other violent death cases autopsy is required in the deaths due to vessel injuries in extremities. Key words: Vascular injuries, Extremity, Forensic autopsy.